Fetal Ascites in a Non-Descript Cow - Patil, Anil (The Indian Journal of Animal Reproduction, 2024)
A case with fetal ascites in cow was treated by obstetrical manoeuvres and the fetus was removed per vaginally. A pluriparous cow was presented with the history of dystocia in the Obstetrical ward, College of Veterinary and Animal  Sciences, Udgir. The case was handled by a local quack for 8 hours but failed to relieve the dystocia. Per vaginum revealed no  placental fluid in the uterus and complete genital passage was dried. The case was diagnosed as fetal ascites and by applying  Obstetrical manoeuvres, the fetus was removed per vaginally which depicted an ample amount of fluid in the abdominal cavity. Key words: Cattle, Dystocia, Fetal ascites.
Keywords: Cattle; Dystocia; fetal ascites